Kojic Acid from the Ethyl Acetate Fraction of Terminalia catappa Linn Fruit Flesh and its anti-cancer activity against HeLa cells - Chasani, Moch.; Widyaningsih, Senny; Rastuti, Undri; Hanafi, Muhammad; Fauzi, Kevin Azhar; Azahra, Silena (Universitas Jenderal Soedirman, 2025)
ABSTRACT. The ethyl acetate fraction of Terminalia catappa Linn. fruit flesh has anti-cancer activity against HeLa cells, with IC50 value is =165.37 ppm. The aim of this research is to isolate active anticancer compound from the ethyl acetate fraction of T. catappa fruit flesh. Anti-cancer active compounds from the ethyl acetate fraction of T. catappa fruit flesh were purified using column chromatography and continued with recrystallization. The compound isolate from the ethyl acetate fraction is clear yellowish crystals and has a melting point 150 ± 2 oC, has anti-cancer activity against HeLa cells of IC50 =413.695 ppm. Results of molecular structure identification using UV spectroscopy; FTIR; 1HNMR, 13CNMR and LC-MS are thought to be the compound 5-Hydroxy-2-(hydroxymethyl)-4H-pyran-4- one (Kojic acid) with a molecular weight of 142.36 gram/mol. The Kojic acid content in T. catappa Linn fruit flesh was found to provide information on the potential use of T. catappa fruit flesh extract in the pharmaceutical and cosmetics industries. Keywords: Anticancer activity, HeLa cells, Kojic acid, T. catappa Linn.